Variations in δ13C of water–soluble leaf and phloem organic matter of Platycladus orientalis: influences of photosynthetic and post–photosynthetic fractionation. Issue 5 (28th May 2019) - Zhang, Yonge; Yu, Xinxiao; Chen, Lihua; Jia, Guodong; Chen, Ran
ABSTRACT: Analysis of variations in water–soluble organic matter (WSOM) δ 13 C of leaves and phloem can efficiently describe the δ 13 C distributions within plants and identify the temporal variation of δ 13 C. In this study, WSOM δ 13 C values of both leaves and phloem (twig, stem, and root) of Platycladus orientalis were measured during seven sunny days, including 2–hour interval measurements at three days for diel pattern analysis and 6–hour interval measurements at the remaining four days for day–to–day variation analysis. Analysis of WSOM δ 13 C in different plant organs showed that 13 C was generally depleted from leaves to twigs, then enriched in stems and subsequently depleted in roots. Stems were significantly 13 C–enriched compared to twigs ( p  < 0.05), while δ 13 C differences between stems and other organs and among leaves, twigs and roots were not significant ( p  > 0.05). No clear diel patterns in δ 13 C of leaves and phloem were found. Daily average δ 13 C values indicated that all plant organs had more positive values on sunny days during the dry season than during the wet season. Both photosynthetic and post–photosynthetic fractionation influence variations in WSOM δ 13 C. These results have implications for research on plant physiology and plant water use.